Rancang Bangun Mesin Pembuat Makaroni dengan Penggerak Motor Listrik 1 HP - Sudirman, Zainal; Fuadi, muhammad Ghufron; Tahir, Haerani (Universitas Muria Kudus, 2025)
Abstract - The advancement of technology in the modern era has significantly driven the adoption of machinery in the food industry to enhance production efficiency, product consistency, and cost-effectiveness. Among the various processed food products, macaroni—produced primarily from wheat flour—has gained popularity due to its unique texture, taste, and adaptability to various culinary applications. However, in Indonesia, small and medium-sized enterprises (SMEs) often rely on raw macaroni materials supplied by large manufacturers, which increases dependency and production costs. This study presents the design and development of a compact macaroni-making machine driven by a 1 HP electric motor, aimed specifically at empowering SMEs to produce macaroni independently. The machine is engineered to produce elbow-shaped macaroni and is capable of achieving a production rate of 23 kilograms per hour. The design methodology involves the calculation of required torque and rotational speed, selection of appropriate materials, and integration of essential components such as the extrusion barrel, screw conveyor, cutting mechanism, and a power transmission system using pulleys and belts. Performance evaluations were conducted to assess the mechanical reliability and production output of the machine. Results indicate that the machine performs consistently under continuous operation, with an average production output of 306.5 grams per minute. Additionally, a cost analysis reveals that the total machine fabrication cost is Rp 5,225,500, with a break-even point (BEP) achieved after processing approximately 1,520 kilograms of macaroni, equivalent to about 12 operational days. This innovation offers an accessible and affordable solution for SME players in the food processing sector, aiming to reduce dependency on large suppliers and improve production autonomy. The study concludes that the proposed machine can significantly contribute to enhancing the productivity and profitability of small-scale food industries. Keywords: macaroni making machine, 1 HP electric motor, extruder, small and medium industries.